Analisis Dampak Manajemen Laba dan Struktur Modal terhadap Nilai Perusahaan : Studi Empiris pada Emiten Food and Beverage yang Terdaftar di BEI - Kesa Anggi Puspita Wardani; Dika Puspitaningrum (AKUNTANSI 45, 2026)
This study aims to analyze the effect of Earnings Management and Capital Structure on Company Value in Food and Beverage issuers listed on the Indonesia Stock Exchange. The main issue raised is the inconsistent results in previous studies regarding the relationship between the variables of Earnings Management and Capital Structure with Company Value. This study uses a quantitative approach with multiple linear regression analysis. The research sample consists of 43 Food and Beverage issuers during the 2021-2023 period, with a total of 129 sample data. Secondary data was obtained from company financial reports. Statistical test results show that both Profit Management and Capital Structure partially have a significant effect on Company Value. These findings indicate that profit management practices and financing policies are highly relevant in shaping investor perceptions. The implications of this study are to provide a deeper understanding for investors and managers in strategic decision-making, as well as a basis for further research to explore other variables that may affect company value.